Fa’aliyah Ta’lim Maharah al-Kalam Li Thalabah Qism Ta’lim al-Lughah al-‘Arabiyah bi Jami’ah al-Islamiyah al-Hukumiyah Kerinci ‘Ala Asas al-Thariqah al-As’ilah wa al-Ajwibah - Fikri, Ahmad (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This research aims to know about the effectiveness of teaching the skill of speech for students of the Department of Teaching Arabic Language at the Islamic State University Kerinci on the basis of the method of questions and answers. Traditional understanding in the process of teaching speaking skills has had a negative impact on students majoring. Problematika felt is the student's disinterest in studying it so many of them do not follow the learning. The study used experimental and quantitative shorts in analyzing data on the effectiveness of speaking skills learning for Arabic Language Education Students at Kerinci Islamic State University based on question and answer methods. The tools in data collection are: tribal testing and dimension testing. Researchers set tribal tests and dimensions during the search. To analyze the level of differences generated between tribal test results and dimension tests, researchers tested t-tests. The results of the study: after performing the calculation of the last results, there was a clear difference between the tribal test results and the dimensions of the experimental group. This means that the application or use of question and answer methods for Arabic Language Education Students at Islamic State University in Kerinci is effective. as evidenced in the following points: 1) It is clear from the tribal test results in the experimental group that they received a level of 42.5, which means that the student's ability in skills 2) It is clear from the dimensional test results in the trial group that the students received an average of 74.58, which means that the student's ability in speaking skills is good.